The Effect of Interest Rate Differentials on Exchange Rate Volatility of East African Community Currencies - Désiré Ntirabampa; Cyrus Iraya (European Scientific Journal, ESJ, 2019)
The study sought to test the effect of interest rate differentials on the exchange rate volatility of East African Community currencies. It used secondary data collected from Central Bank of Kenya, Bank of Uganda, Bank of Tanzania, Bank of the Republic of Burundi, National Bank of Rwanda and the IMF e-Library. A panel data model was used to regress average monthly exchange rates, interest rate differentials, inflation rate differentials and relative current account balances for a period starting from January 2013 to December 2017. Findings from the fixed-effects model showed that 98.8% of the variation in the exchange rate is explained by the three independent variables. Interest differential was the main independent variable with a coefficient’s value of 0.0274. This means that in East African Community an increase by 1 point in interest rate differential leadsto the depreciation of home currency by 0.0274 points. The study also found that the relative current account balance contributes also to the home currency depreciation with a coefficient’s value of 0.000052. However, the study could not be able to find the expected results for inflation differential as it has a negative coefficient’s value (-0.0075). This contradicts the economic theory on inflation differential and may due to other variables that were not included in the model but can be with great importance in the explanation of exchange rate movement. The study further suggested that more research can be carried out to bring forth more knowledge to the pool of literature on the relationship between interest rate differential and exchange rate volatility in the region.